Juridical Review of the Formulation of Criminal Sanctions Against Narcotics Crime Actors Based on Positive Criminal Law - Sandika Dwi Nugroho; Arpangi Arpangi (UNISSULA Semarang, 2021)
The purpose of this study is to describe, examine, and analyze the formulation of criminal sanctions against narcotics criminals based on positive criminal law and the weaknesses of the formulation of criminal sanctions against narcotics criminals based on positive criminal law and policies for formulating criminal sanctions against narcotics criminals in reform future criminal law. This study uses a normative juridical approach. The results of the study state that (1) The formulation of criminal sanctions against narcotics criminals in Law Number 35 of 2009 is regulated in Article 111 - Article 148, with the provisions: (a) sanctions in the form of crime and action; (b) criminal sanctions in the form of capital punishment, imprisonment, confinement, and fines as well as additional penalties in the form of: revocation of certain rights against corporations; (c) action sanctions in the form of medical and social rehabilitation as well as expulsion and prohibition from entering Indonesia for foreigners; (d) the number/length of criminal sanctions varies; (e) criminal sanctions are formulated in single, alternative, cumulative and combination forms; (f) there is a specific minimum criminal penalty; (g) the weighting of the crime; (g) trial and conspiracy shall be punished with the same crime as committing a crime; and (h) a fine that cannot be paid, is sentenced to a maximum imprisonment of 2 years. (2) the weaknesses of the policy on the formulation of criminal sanctions in Law Number 35 of 2009 are: (a) criminal sanctions are formulated in a cumutative manner, there are no rules for corporations that do not pay fines and the types of sanctions are not specific; (b) a minimum criminal threat specifically deviating from the Criminal Code system,